1998
DOI: 10.1086/520307
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Active Cytomegalovirus Infection Among Septic Patients

Abstract: Cytomegalovirus (CMV) infection is an important cause of disease in immunocompromised patients. In a prospective longitudinal study of 34 septic patients, the incidence of active CMV infection was examined. Eleven of 34 patients (32.4%) had active CMV infection, diagnosed by immunocytochemical staining of CMV pp65 antigen in blood leukocytes and/or detection of CMV DNA by PCR. Positive results for CMV infection were obtained in a median of 4 days (by PCR) or 11 days (by staining of pp65 antigen) after onset of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
121
2
8

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(140 citation statements)
references
References 31 publications
(5 reference statements)
7
121
2
8
Order By: Relevance
“…Allograft rejection, sepsis, acute illness, IL-6 and TNF have long been implicated in reactivation of HCMV in patients (Cook et al, 1998;Döcke et al, 1994;Fietze et al, 1994;Grattan et al, 1989;Heininger et al, 2001;Hibberd et al, 1992;Kalil & Florescu, 2009;Kutza et al, 1998;Lao et al, 1997;Limaye et al, 2008;Mutimer et al, 1997;Portela et al, 1995;Razonable et al, 2001;Reinke et al, 1994a) and allogeneic stimulation, TNF, IL-6 and lipopolysaccharide have been shown to induce reactivation of HCMV in experimental models (Hargett & Shenk, 2010;Huang et al, 2012;Kew et al, 2014;O'Connor & Murphy, 2012;Reeves & Compton, 2011;Söderberg-Nauclér et al, 1997). Allogeneic transplantation and TNF are sufficient to activate both an HCMV MIEP-lacZ transgene and MCMV IE gene expression (Hummel et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allograft rejection, sepsis, acute illness, IL-6 and TNF have long been implicated in reactivation of HCMV in patients (Cook et al, 1998;Döcke et al, 1994;Fietze et al, 1994;Grattan et al, 1989;Heininger et al, 2001;Hibberd et al, 1992;Kalil & Florescu, 2009;Kutza et al, 1998;Lao et al, 1997;Limaye et al, 2008;Mutimer et al, 1997;Portela et al, 1995;Razonable et al, 2001;Reinke et al, 1994a) and allogeneic stimulation, TNF, IL-6 and lipopolysaccharide have been shown to induce reactivation of HCMV in experimental models (Hargett & Shenk, 2010;Huang et al, 2012;Kew et al, 2014;O'Connor & Murphy, 2012;Reeves & Compton, 2011;Söderberg-Nauclér et al, 1997). Allogeneic transplantation and TNF are sufficient to activate both an HCMV MIEP-lacZ transgene and MCMV IE gene expression (Hummel et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a greater understanding of the molecular events controlling reactivation from latency is needed to develop alternative strategies to prevent CMV disease. Döcke et al, 1994;Fietze et al, 1994;Grattan et al, 1989;Heininger et al, 2001;Hibberd et al, 1992;Kalil & Florescu, 2009;Kutza et al, 1998;Lao et al, 1997;Limaye et al, 2008;Mutimer et al, 1997;Portela et al, 1995;Razonable et al, 2001;Reinke et al, 1994aReinke et al, , 1994b) and the inflammatory cytokine TNF has been proposed to drive reactivation through NF-k B-mediated activation of the major immediate early promoter (MIEP) (Döcke et al, 1994;Fietze et al, 1994;Prösch et al, 1995;Stein et al, 1993). However, due to the species specificity of HCMV, it has not been possible to test this hypothesis in the context of organ transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…CMV has been shown to suppress T cells, NK cells, macrophages, neutrophils and dendritic cells 38,[43][44][45] and is clinically associated with death in cases of bacterial and fungal infection. 32,38,46 It was somewhat surprising, however, that the impact of a CMV infection lasts for such a long time after HSCT. Although several patients experienced repeated reactivation during the early phase after HSCT, we did not routinely monitor CMV for longer than 6 months after HSCT, so we do not know if the patients experienced repeated and/or prolonged CMV reactivation contributing to the long-term risk of fatal infections.…”
Section: Discussionmentioning
confidence: 99%
“…CMV infection increases the expression of cytokines such as TNF-a, IL-6, and IL-8 (17,18). Observations of clinical samples showed that the increased serum levels of TNF-a seen in patients with sepsis and atopic dermatitis were related to activation of latent HCMV (19,20). Expression of IL-6 and granulocyte-macrophage colony-stimulating factor (GM-CSF) are involved in HCMV-mediated angiogenesis, and may contribute to the development of HCMV-associated vascular diseases (21).…”
Section: Discussionmentioning
confidence: 99%